Efficiency of thiamethoxam for coffee leaf-miner control. I - Influence of the mode of application - Souza, Júlio César de; Reis, Paulo Rebelles; Rigitano, René Luis de Oliveira; Ciociola Júnior, Américo Iorio (Coffee Science - ISSN 1984-3909, 2007)
The coffee leaf-miner Leucoptera coffeella (Guérin-Mèneville, 1842) (Lepidoptera: Lyonetiidae) is the most important insect pest of coffee (Coffea arabica L.) in Brazil, where reductions in the production can reach 70 %. Its control using granular formulations of systemic insecticides, which are soil-applied in the rainy season, has shown to be erratic over the last years, attributed to the irregular distribution of rainfall. As water-dispersible granules (WG) formulations of insecticides can be applied in different forms and are less dependent on the soil moisture, this work was carried out to assess the influence of the mode of application of thiamethoxam WG for the control of coffee leaf-miner in the cerrado region of Minas Gerais State. The experiment consisted of eight treatments and four replicates, in a randomized blocks statistical design. The treatments were: thiamethoxam 250 WG (applied as drench at the plant base, drench in soil furrows and drip irrigation), imidacloprid 700 WG (drench at the plant base and as drip irrigation), thiamethoxam 10 GR and aldicarb 150 GR (in soil furrows), and control. Application was performed in February, with monthly evaluations on pest control until July. Drench treatments at plant base as well as drip irrigation with thiamethoxam 250 WG provided high control efficiency for about 130 days. The thiamethoxam concentrations in the leaves from these treatments were higher than in leaves from other treatments with other modes of application of the insecticide.